Tumor islands and spread through air spaces: Distinct patterns of invasion in lung adenocarcinoma. Issue 1 (8th December 2015) - Morales‐Oyarvide, Vicente; Mino‐Kenudson, Mari
Abstract : Lung adenocarcinoma is a highly heterogeneous disease and the heterogeneity is associated with various patient outcomes even in early‐stage tumors. In order to improve prognostic and predictive values, the IASLC/ATS/ERS international multidisciplinary lung adenocarcinoma classification was put forth in 2011 and it has been adopted in the recently published World Health Organization (WHO) classification of Tumours of the Lung, Pleura, Thymus and Heart 4th edition 2015, and lung adenocarcinomas are classified based on the predominant pattern. The performance of the classification in stratifying patient outcomes after resection of Stage I tumors and predicting molecular alterations has been confirmed by several studies. It also includes the category of minimally invasive adenocarcinoma (MIA) that predicts 100% 5‐year recurrence free survival after curative resection similar to adenocarcinoma in situ . The diagnosis of MIA is based on not only size of the invasive component but also the absence of aggressive morphologic features such as pleural and/or lymphovascular invasion. Importantly, the WHO 2015 classification has introduced the concept of air space invasion and includes it as the exclusion criteria for MIA. The air space invasion consists of tumor islands and spread through air spaces (STAS). In this review, we will discuss the two entities and their clinical implications.